The Religious Persecution of Casa do Rei e Senhor das Alturas - De Sousa, Vilson Caetano (Journal of Africana religions, 2021)
This essay recounts how a Candomblé terreiro in Salvador, Bahia, Brazil, was harassed by a neighbor. By lodging fictitious or exaggerated complaints to the authorities, neighbors harness the power of the state to support their intolerance against Afro-Brazilian religions.